The diagnostic value of non-invasive methods for diagnosing bladder outlet obstruction in men with lower urinary tract symptoms: A meta-analysis - Cheng, Yu; Li, Taicheng; Wu, Xiaoyu; Ling, Qin; Rao, Ke; Yuan, Xiaoyi; Chen, Zhong; Du, Guanghui; Xu, Shengfei (Frontiers in Surgery, 2022)
Purpose: We conducted the first meta-analysis to determine the diagnostic value of non-invasive methods for diagnosing bladder outlet obstruction (BOO) in men with lower urinary tract symptoms (LUTS). Methods: We searched a range of databases for relevant publications up to June 2022, including PubMed, Embase, Web of Science, and the Cochrane Library. Retrieved studies were then reviewed for eligibility and data were extracted. The risk of bias (RoB) was assessed using the QUADAS-2 tool. We then performed a formal meta-analysis to evaluate the accuracy of various non-invasive methods for diagnosing BOO in men. Results: We identified 51 eligible studies including 7897 patients for meta-analysis. The majority of the studies had a low overall RoB. Detrusor wall thickness (DWT) (pooled sensitivity (SSY): 71%; specificity (SPY): 88%; diagnostic odds ratio (DOR): 17.15; area under curve (AUC) 0.87) and the penile cuff test (PCT) (pooled SSY: 87%; SPY: 78%; DOR: 23.54; AUC: 0.88) showed high accuracy for diagnosing BOO. Furthermore, data suggested that DWT had the highest pooled SPY (0.89), DOR (32.58), and AUC (0.90), when using 2 mm as the cut-off. Conclusions: Of the non-invasive tests tested, DWT and PCT had the highest levels of diagnostic accuracy for diagnosing BOO in men with LUTS. DWT, with a 2 mm cut-off, had the highest level of accuracy. These two methods represent good options as non-invasive tools for evaluating BOO in males.